Le logis du Grand Sacristain de l’abbaye Saint-Michel de Cuxa, Codalet (Pyrénées-Orientales) - Patrice Alessandri; Astrid Huser; Aline Molinier (Archéologie Médiévale)
Built at the foot of the Canigou range in the Pyrenees, the Abbey of Saint-Michel de Cuxa is one of the rare examples of the transition from Southern Pre-Romanesque to Romanesque art. The transformation of the original monastic foundation during the eleventh century is seen in the originality of the architectural solutions implemented in this major monument of Western Christianity.Half a century after the last excavations were completed, through multidisciplinary interpretation associating topography, sample area excavations, standing building studies and documentary research, an archaeological operation on the Grand Sacristan’s abode has provided a new picture of the structural transformations between the tenth and eighteenth centuries. Four main phases of the history of the abbey have thus been distinguished.